Mild closed head injury promotes a selective trigeminal hypernociception: Implications for the acute emergence of post‐traumatic headache. (29th August 2014) - Benromano, T.; Defrin, R.; Ahn, A.H.; Zhao, J.; Pick, C.G.; Levy, D.
Abstract Background Headache is one of the most common symptoms following traumatic head injury. The mechanisms underlying the emergence of such post‐traumatic headache (PTH) remain unknown but may be related to injury of deep cranial tissues or damage to central pain processing pathways, as a result of brain injury. Methods A mild closed head injury in mice combined with the administration of cranial or hindpaw formalin tests was used to examine post‐traumatic changes in the nociceptive processing from deep cranial tissues or the hindpaw. Histological analysis was used to examine post‐traumatic pro‐inflammatory changes in the calvarial periosteum, a deep cranial tissue. Results At 48 h after head injury, mice demonstrated enhanced nociceptive responses following injection of formalin into the calvarial periosteum, a deep cranial tissue, but no facilitation of the nociceptive responses following injection of formalin into an extracranial tissue, the hindpaw. Mice also showed an increase in the number of activated periosteal mast cells 48 h following mild head trauma, suggesting an inflammatory response. Conclusion Our study demonstrates that mild closed head injury is associated with enhanced processing of nociceptive information emanating from trigeminal‐innervated deep cranial tissues, but not from non‐cranial tissues. Based on these finding as well as the demonstration of head injury‐evoked degranulation of calvarial periosteal mast cells, we propose that inflammatory‐evoked enhancement of peripheral cranial nociception, rather than changes in supraspinal pain mechanisms play a role in the initial emergence of PTH. Peripheral targeting of nociceptors that innervate the calvaria may be used to ameliorate PTH pain.